Development of an IoT-based hand gesture monitoring system for disabled person using flex sensor - Mohd Noh, Zarina; Ismail, Nurfarah Izzati; Mohamad Yatim, Norhidayah (Penerbit Universiti Teknikal Malaysia Melaka, 2023)
The Internet of Things(IoT) has revolutionized various healthcare technologies, enabling innovative solutions for monitoring, and assisting disabled people. In this paper, a method for utilizing IoT and flex sensors to develop a hand gesture monitoring system for disabled persons who cannot communicate verbally will be presented. By adapting wearable technology on glove, the system captures hand gestures to facilitate communication and enhance caretaker monitoring. The IoT-based platform used is Blynk, which was connectedvia the ESP8266 Wi-Fi module through the Arduino Uno board with flex sensors fixed on the glove. The flex sensors measured the resistance value produced when the sensors were bent according to hand gestures, to trigger the alarm on Arduino Uno and notifications in the Blynk apps. These notifications provide real-time updates of the disabled person’s hand gestures. Consequently, caretakers can remotely monitor the disabled person needs without requiring constant presence around the disabled person.